1986
DOI: 10.1007/bf01732189
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a cod liver oil diet in healthy and insulin-dependent diabetic volunteers on fatty acid pattern, inhibition of prostacyclin formation by low density lipoprotein (LDL) and platelet thromboxane

Abstract: Ten healthy and twenty diabetic volunteers (type 1) received 15 capsules (à 450 mg) cod liver oil for 2 weeks daily in addition to a "normal" diet. The levels of eicosapentaenoic acid in the plasma phospholipids of both groups were increased after the treatment. The inhibition of the prostacyclin formation by LDL was diminished when the LDL was isolated after the treatment in comparison to LDL taken in the same concentration and from the same donors before it. The thromboxane B2 (TXB2) synthesis capacity of cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…This is despite numerous studies in which fish oil supplementation has been examined in both non-insulin-dependent diabetic (NIDDM; [10][11][12][13] and IDDM subjects (14)(15)(16)(17). The most consistent Serum lipids in patients without retinopathy (A; n = 10) and with retinopathy (B; n = 6) during baseline, after 3 wk treatment with Max EPA, and 6 wk after ceasing Max EPA.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This is despite numerous studies in which fish oil supplementation has been examined in both non-insulin-dependent diabetic (NIDDM; [10][11][12][13] and IDDM subjects (14)(15)(16)(17). The most consistent Serum lipids in patients without retinopathy (A; n = 10) and with retinopathy (B; n = 6) during baseline, after 3 wk treatment with Max EPA, and 6 wk after ceasing Max EPA.…”
Section: Discussionmentioning
confidence: 94%
“…However, when a greater quantity of w3FA was used, there was a decrease in total cholesterol (12). Small quantities of co3FA (<1 g EPA/day) had no effect on cholesterol and lipoproteins in both NIDDM and IDDM subjects (13)(14)(15).…”
Section: Effect Of Max Epa On Apolipoproteins (Apo) A-l A-ll and B mentioning
confidence: 92%
See 1 more Smart Citation
“…Blood pressure and vascular compliance Blood pressure was unaltered in several studies of type 1 diabetic patients (83,84,86) and only decreased in one controlled study (90). Also in patients with type 2 diabetes, blood pressure was largely unaltered by supplementation with n-3 fatty acids (104).…”
Section: Hemostasismentioning
confidence: 99%
“…In patients with type 1 diabetes, dietary n-3 fatty acids decrease platelet reactivity (83)(84)(85)(86)(87)(88), without changing plasma fibrinogen levels (89 -92) or other coagulation parameters (84,92,93). One study in type 1 diabetic subjects showed increased levels of type 1 plasminogen activator inhibitor (PAI-1) (an endogenous inhibitor of fibrinolysis) after supplementation with n-3 fatty acids (92).…”
Section: Hemostasismentioning
confidence: 99%